2014
DOI: 10.1088/2041-8205/781/1/l20
|View full text |Cite
|
Sign up to set email alerts
|

A New Stellar Chemo-Kinematic Relation Reveals the Merger History of the Milky Way Disk

Abstract: The velocity dispersions of stars near the Sun are known to increase with stellar age, but age can be difficult to determine, so a proxy like the abundance of α elements (e.g., Mg) with respect to iron, [α/Fe], is used. Here we report an unexpected behavior found in the velocity dispersion of a sample of giant stars from the Radial Velocity Experiment survey with high-quality chemical and kinematic information, in that it decreases strongly for stars with [Mg/Fe] > 0.4 dex (i.e., those that formed in the first… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 36 publications
6
70
1
Order By: Relevance
“…This work illustrates the effect that more robust definitions of MW stellar populations (allowed by methods such as the t-SNE; Anders et al 2018, Chiappini et al in prep) can have on the recent claim that a Li decline in super-solar metallicity stars found by many authors (Delgado Mena et al 2015;Guiglion et al 2016;Fu et al 2018) would imply a revision of the lithium stellar yields at high metallicities. As shown in Anders et al (2018) and Chiappini et al (in prep), the most metal-rich thin-disk stars have most probably migrated from inner disk regions (as has been indicated by previous observations such as Casagrande et al (2011), Trevisan et al (2011), and Anders et al (2017b; see the discussion in Chiappini 2015), and cannot be modeled as part of a local thin disk without taking into account the fact that stars move out of their birth places, as is clearly shown by chemodynamical models (Minchev et al 2013, 2014band Minchev et al 2018. It is also consistent with the kinematics found in super-solar metallicity stars in the solar neighborhood, see, e.g., Wojno et al (2018).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…This work illustrates the effect that more robust definitions of MW stellar populations (allowed by methods such as the t-SNE; Anders et al 2018, Chiappini et al in prep) can have on the recent claim that a Li decline in super-solar metallicity stars found by many authors (Delgado Mena et al 2015;Guiglion et al 2016;Fu et al 2018) would imply a revision of the lithium stellar yields at high metallicities. As shown in Anders et al (2018) and Chiappini et al (in prep), the most metal-rich thin-disk stars have most probably migrated from inner disk regions (as has been indicated by previous observations such as Casagrande et al (2011), Trevisan et al (2011), and Anders et al (2017b; see the discussion in Chiappini 2015), and cannot be modeled as part of a local thin disk without taking into account the fact that stars move out of their birth places, as is clearly shown by chemodynamical models (Minchev et al 2013, 2014band Minchev et al 2018. It is also consistent with the kinematics found in super-solar metallicity stars in the solar neighborhood, see, e.g., Wojno et al (2018).…”
Section: Resultsmentioning
confidence: 69%
“…As clearly shown by both observations (e.g., Casagrande et al 2011;Trevisan et al 2011;Anders et al 2017a) and chemodynamical models (Minchev et al (2013(Minchev et al ( , 2014b, the most metal-rich stars (those with [Fe/H] > 0.25) are typically 5-10 Gyr old. Therefore all of them will have depleted their lithium by large amounts (as discussed in 3.1).…”
Section: Effect Of Radial Migrationmentioning
confidence: 86%
See 1 more Smart Citation
“…The r birth − σz relation was first presented in order to understand why the velocity dispersion increase with [Mg/Fe] in RAVE Giants and SEGUE G-dwarfs showed an abrupt drop at the highest [Mg/Fe] end (Minchev et al 2014b). It was found that the observations could be explained by kinematically cool, old (thus low metallicity and high [Mg/Fe]) stars arriving to the solar neighborhood from low Galactic radii (∼ 2 − 4 kpc).…”
Section: Birth Radius Vs Vertical Velocity Dispersionmentioning
confidence: 99%
“…In principle age is the parameter with the most power to discriminate among models of our Galaxy's history (e.g. Minchev et al 2014). However, stellar ages have only recently started being derived with reasonable error bars, and for only a relatively small sample of stars, and potential biases in the derived ages may still exist (Miglio et al 2013).…”
Section: Introductionmentioning
confidence: 99%